Macromedia Dreamweaver MX 2004 magic - Foti, Massimo (Magic Ser., 2004)
As a serious Web designer or developer, you'll want to do one thing and one thing only when you lay your hands on the latest version of Dreamweaver: Start tinkering with all its new features. Problem is that's hard to do on someone else's dime. With Dreamweaver MX 2004 Magic, you don't have to! In these pages, Dreamweaver wizards Mossimo Foti, Angela C. Buraglia, and Daniel Short and several other experts draw on their own professional experience to offer 12 real-world projects that let you explore Dreamweaver MX 2004 at your leisure. With a focus on areas that can be troublesome for professional users-whether because they present thorny issues or because they draw on completely new features-each lesson provides need-to-know tips, proven techniques, and best practices. By working through the step-by-step tutorials (whose project files and code you'll find on the accompanying CD), you soon will be finding your way around all of Dreamweaver MX 2004's new features: dynamic cross-browser validation, improved CSS support, built-in graphics editing, and more. In addition to the code listings and exercise files on the CD-ROM, you¿ll find videos that clearly demonstrate step by step all the procedures you need to complete in order to create the projects.